We know that Slope of a Line Passing through two points (x₁ , y₁) and (x₂ , y₂) is given by :
![Slope(m) = (y_2 - y_1)/(x_2 - x_1)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/evx98xg5pdm9jgzronb0t9o8a6c9vz4utw.png)
Given Points are (-1 , 4) and (3 , -4)
here x₁ = -1 and x₂ = 3 and y₁ = 4 and y₂ = -4
⇒
![Slope = (-4 - 4)/(3 + 1) = (-8)/(4) = -2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/yjwebkuqf2k3bjqll2qm9h7wse8xahiz1m.png)
We know that the form of line passing through point (x₀ , y₀) and having slope m is :
y - y₀ = m(x - x₀)
Here the line passes through the point (3 , -4)
x₀ = 3 and y₀ = -4 and we found m = -2
Equation in Point slope form : y + 4 = -2(x - 3)
First Option is the Answer